g(x)=4f(x)-1

Simple and best practice solution for g(x)=4f(x)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g(x)=4f(x)-1 equation:


Simplifying
g(x) = 4f(x) + -1

Multiply g * x
gx = 4f(x) + -1

Multiply f * x
gx = 4fx + -1

Reorder the terms:
gx = -1 + 4fx

Solving
gx = -1 + 4fx

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by 'x'.
g = -1x-1 + 4f

Simplifying
g = -1x-1 + 4f

Reorder the terms:
g = 4f + -1x-1

See similar equations:

| 2=15*x | | 12a+3+2a-1= | | 750-50x=-185-35x | | 2-(2*y)=y+64 | | 7x^2-4+x=15x | | 2=110*x | | y-5=y-9 | | 6x^2-4x+0=0 | | 53-x+8=4x-27+1 | | (2w+3)2+2x=42 | | 3(7-2k)=57 | | -8+4m^2-5m^2= | | 7x+3-2x+9=47 | | z-8.4=4 | | (x+(2+i))(x+(2-i))=0 | | -0.2(212-h)=8.6 | | 5x-10=39 | | 5.25b=22.75 | | -5x-2=-x-7 | | 3(x+1)+3(x+3)= | | 14x-(4x-5)=45 | | 7x-26=2x+54 | | -7(5k-5)=-210 | | 25-3u=24 | | 95=5X+2X+7 | | 2=10-1.6d | | 95=5X+2X+7 | | 95=5X+2X+6 | | 95=5X+2X+6 | | 5x-3(x-5)=-8+4x+17 | | 95=5X+2X+6 | | 6u-40=3(u+4)-4 |

Equations solver categories